Importance of VA mycorrhizae for phosphorus supply to pasture plants in tropical Oxisols - Salinas, José G.; Sanz Scovino, José Ignacio; Sieverding, Ewald (Springer, 1985)
Inoculum of the VA mycorrhizal fungusGlomus manihotis was added to an Oxisol containing only a moderate inoculum potential of indigenous VA mycorrhizal fungi. Its effect on growth and P uptake of two pasture plant species was investigated in pot experiments. This effect was studied at a range of P applications, corresponding to 0, 9, 18, 35, 70 and 140 kg P/ha. The plant species used were the grassAndropogon gayanus and the legumePueraria phaseoloides, which were harvested four times,viz. at 70, 100, 130 and 160 days after planting. At first harvest, in the non-inoculated treatments, the first notable response to P application was found with 35 and 70 kg P/ha applied. Addition of inoculum resulted in growth response even at the lowest P application with both plant species. With successive harvests growth response to P application and inoculation disappeared rapidly. However, inoculation resulted in early and extensive development of mycorrhiza, in longer continued P uptake of plants and in a 2 to 4 times higher utilization of added P with both plant species. In the case of no inoculum being added a negative effect of medium and high P applications on mycorrhiza was found in the grass, but not in the legume. In both species the frequency of mycorrhiza increased with time. The slight negative growth response of both plants to the smallest P dressing (9 kg/ha) when no inoculum was applied could be related to the high level of sporulation of indigenous mycorrhizal fungi.